PROSPECTS OF INNOVATIVE ACTIVITY IN THE INDUSTRY FOR THE PERIOD TILL 2020 - M. Motova (Управленческие науки, 2015)
In the article the author has provided the results of the analysis, forecast and development of the main indicators covering innovation activities of the Russian industry. The estimation of the current situation and forecasts results of the innovation development provided in the article is based on the official statistics data. The main source of the statistical information in the field of innovation activities is contained in the report No. 4 on innovation development entitled “Data on innovative activity of an organization”.The forecast is covered by the indicators reflecting the innovative activities of the organizations dealt with industrial production, including in particular the main expenses on technology innovations and shipped innovation goods as well. Besides the data reflecting directly the innovation potential of the industrial organization dealing with the calculation of forecasts was used by the author as the set of macroeconomic indicators. At the analysis phase composition of these indicators is being defi when developing the forecasting models for each of the concrete indicators. This set of indicators includes GDP value, size of the federal budget, structure of its account part, rates of inflation and some other indicators.On the basis of the forecast methodology the author used package of the regression and factorial models making an opportunity to receive forecasts on the basis of the proposed scenario planning conditions of an economic situation in the country. The models used in the methodology are adaptive, i.e. capable to react actively on the dynamic changes in the content of the current forecasting data and herewith taking into account the forecasting results provided in the previous stage.In the article as a result of the calculations the author has given rates of the different types of the economic performance as a function of the efficiency and innovation activities. As a result the list of leaders and outsiders is being worked out. On the basis of the analysis of the current trends and the prognosis of the indicators describing the innovation domain as well the author makes deductions on the perspectives of the innovation development.The research results may be used by federal authorities and business community for the purpose of accepting the management decisions promoting a selection of the directions of the innovation development.